(untitled) (Eurasian Research Bulletin, 2023)
In recent times, incidents of acetic acid poisoning have witnessed a surge, primarily attributed to its easy accessibility. Suicide attempts, wherein acetic acid is frequently employed, constitute a significant factor. Additionally, the issue of alcohol dependence and misuse has become a pressing concern within the population. Government initiatives are directed towards addressing this problem by exerting pressure on producers to raise the prices of alcoholic beverages. Owing to the grip of alcohol addiction, individuals seek alternatives, often resorting to the use of acetic acid. This article will delve into the clinical features and diagnostic criteria associated with acetic acid poisoning.